Learning Motivation and Perceived Social Support as Predictors of Student Engagement Among Ninth-Grade Students - Haliza Maulana; Pratidina Ekanesia; Prinska Damara Sastri (International Journal of Marketing & Human Resource Research, 2026)
This study examined the roles of learning motivation and perceived social support in predicting student engagement among ninth-grade students. A quantitative cross-sectional survey was conducted with 207 students selected randomly from a population of 430 students at SMP X. Data were collected through a questionnaire measuring learning motivation, perceived social support, and student engagement. The instruments showed satisfactory reliability, and the data were analyzed using descriptive procedures, regression assumption testing, and multiple linear regression. The findings indicated that both learning motivation and perceived social support positively and significantly predicted student engagement. Learning motivation showed a stronger contribution than perceived social support, while both variables jointly provided substantial explanatory power for differences in student engagement. These results suggest that students’ involvement in school is influenced by both their internal reasons for learning and their perception that meaningful support is available from people around them. Schools are therefore encouraged to strengthen students’ sense of purpose, persistence, and autonomy in learning while also ensuring access to emotional, informational, appraisal, and practical support from teachers, parents, peers, and school counselors.